Democracia como noção no discurso político-midiático: representações de sujeitos, PDV e imaginários sociodiscursivos na construção da noção de democracia no artigo de opinião - Jaqueline dos Santos Batista Soares (2022)
On assumption that the notion of democracy may be considered as an unfinished concept and always in construction, as well as is the democratic system in many countries, especially in Latin America. In this research, we propose an analysis that aims to describe and interpret how people build representations about the notion of democracy. Besides this, when there is a projection of discourse with the purpose to make see and make think there is an action of reconstructing and/or constructing about the meanings and representations of speakers, enunciators, and the very notion within the scope of media political discourse. It is in the function of the particularities of the notion of democracy understood as a concept constituted by a heterogeneity - in a relationship of transparency and at the same time opacity - from which the subjects can play with the senses that the interest of our research in analyzing how the discursive organization of the opinion article can reflect this opacity of the notion in a communicative situation of public polemic. Accordingly, this polemic situation makes the concept of democracy as a discursive event because it establishes an intensely dialogical and polarized circulation about this concept. Then, for this analysis, we selected a corpus composed of ten opinion articles from the following information media: five from “Folha de São Paulo”, one from “O Globo”, two from “Estadão”, one from “O Tempo”, and one “El País”. In the analysis of these articles, we seek to examine which discursive strategies are used by the subjects in the construction of the point of view on the notion of democracy. Therefore, in this work, our theoretical basis will be the Discourse Analysis has as main approaches the Semiolinguistic Theory; as well as the Interactional Theory from the point of view (dialogical management of voices, enunciative positions, and postures, imputation, and modalization); and argumentation (schematization, problematization, definition, analogies, arguments, conditional, restrictive etc.), with a focus on polemic management that points to the construction of values that support the notion of democracy. From the description and analysis of politicalmedia articles, notions of democracy have emerged customized by a process in which the point of view adopts the perspective desired by the speakers. Such singularity assumes an identity aspect as it seeks to meet the political, ideological and partisan bias of different groups in order to persuade, convince and justify different subjects' actions (ou - different players' actions).In this sense, the significant face of the notion of democracy moves away from a socially convention, socially shared and homogeneous cognition and starts to be shaped by a cognitive understanding that particularizes its meanings.